ANALISIS LAPORAN ARUS KAS SEBAGAI PENDUKUNG DALAM PENGAMBILAN KEPUTUSAN INVESTASI (Studi di Perusahaan Industri Rokok yang Terdaftar di Bursa Efek Indonesia) - M.Si, Drs. Supriadi; Sari, Riza Diana Efria (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
This study aims to assist investors in making investment activities through cash flow ratio analysis on cigarette companies listed in Indonesia Stock Exchange (IDX) from 2012 to 2014 consisting of 4 companies PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk, PT Bentoel International Investama and PT Wismilak Inti Makmur Tbk.        Cash flow statement is one part of the financial statements can be devastating for investors because it provides information to investors and creditors and other users of financial potential in making investment decisions.        Data used are the financial statements of each company's population, which was published through the website www.idx.co.id. The method of data analysis used in this study was descriptive quantitative method, using a ratio based on cash flow analysis which consists of the liquidity ratios, solvency ratios, and investing capital expenditure ratio, and cash flow return ratio.        Judging from the calculation of the ratio analysis above, of the four companies that serve as population of PT Hanjaya Mandala Sampoerna Tbk showed a better value than other companies and more deserving of investment from potential investors.